The Causal Effect of Market Priming on Trust: An Experimental Investigation Using Randomized Control - Al-Ubaydli, Omar (Public Library of Science, 2013)
We report data from laboratory experiments where participants were primed using phrases related to markets and trade. Participants then participated in trust games with anonymous strangers. The decisions of primed participants are compared to those of a control group. We find evidence that priming for market participation affects positively the beliefs regarding the trustworthiness of anonymous strangers and increases trusting decisions.